2018
DOI: 10.1021/acs.orglett.7b03662
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Aggregation-Induced Emission from Free Rotation Restriction of Double Bond at Excited State

Abstract: This paper reports that cis-TPE dicycles emit strong fluorescence, while the gem dicycles show almost no emission in solution, demonstrating that the free rotation restriction of the double bond at the excited state is the key factor for AIE effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(65 citation statements)
references
References 32 publications
(38 reference statements)
3
60
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] The recently discovered aggregation-inducede mission (AIE) has become one of top research frontiers in chemistry and materials due to great potential in solid emitter andc hemo/biological sensors. [9][10][11][12][13] Up to now,al arge number of sensors based on AIEgens have been developed. [14][15][16][17][18][19][20] Some of them show valuablea pplication prospecti nm onitoring,a nalysis, imaging of ions.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The recently discovered aggregation-inducede mission (AIE) has become one of top research frontiers in chemistry and materials due to great potential in solid emitter andc hemo/biological sensors. [9][10][11][12][13] Up to now,al arge number of sensors based on AIEgens have been developed. [14][15][16][17][18][19][20] Some of them show valuablea pplication prospecti nm onitoring,a nalysis, imaging of ions.…”
mentioning
confidence: 99%
“…Xiong et al observed an interesting phenomenon of TPE derivatives, as shown in Figure 4a. [44] When the phenyl groups of TPE were connected by short rigid tethers, the resultant TPE tetracycle emitted strong fluorescencei ns olution. Through an elaborate chemical design, they found that cis-TPE bicycles (1, 2, and 5) emitted strong green, yellow,a nd green emissions, respectively,w hereas gem-TPE bicycle( 3, 4, and 6) did not ex-hibit fluorescencei nT HF solution under the irradiation of aU V lamp (l = 365 nm;F igure 4b).…”
Section: Rir Versus Z/e Isomerizationmechanism For Tpe Derivativesmentioning
confidence: 99%
“…C) Representation of double-bond rotationint he excitedstate. Reproduced with permission from Ref [44]…”
mentioning
confidence: 99%
“…Although the intramolecular rotation is generally related to the rotation of a single bond, Xiong et al 41 proved the rotation of a double bond at the excited state will result in the fluorescence quenching of AIEgens in solution. They synthesized a series of TPE macrocycles to observe their fluorescence in tetrahydrofuran solution, because the TPE has simple molecular structure but splendid AIE characteristics.…”
Section: Restriction Of Intramolecular Motionmentioning
confidence: 99%